A Textbook of Psychology - Hebb, Donald Olding (W.B. Saunders, 1966)
"About six years ago I took a new look at the introductory course in psychology and finding no textbook that covered what I wanted in subject matter, was driven to write one. This book is the result. In it I attempt to clarify and codify the ideas which make up the main structure of psychological theory in ways that will be intelligible to the beginning student and at the same time reasonably rigorous. In doing so I have omitted (or treated very succinctly) matters that have traditionally made up a good proportion of the introductory course; and have included others that are, as far as I know, here stated formally for the first time. My object has been to include the ideas and information needed for the understanding of psychological problems, as far as this is feasible in an introductory textbook, and to exclude the merely traditional. The raison d'°tre of the content, the underlying philosophy of science, will be found in Chapters 1 and 13. Psychology is fundamentally a biological science, not a social science, nor a profession; out of it have grown social psychology and applied psychology, both of which now exist in their own right as disciplines distinct from the parent stem--and yet maintaining their organic relation with it. The relation exists because both demand a solid understanding of the mechanisms of behavior in the individual subject. The student's approach to either social or applied psychology, therefore, is through the ideas of "biological" psychology--the theories of learning, perception, emotion and so on which are biological because they have always been profoundly influenced by neurophysiology, neuroanatomy, and evolutionary and genetic theory. This book is meant both for the student who will go on to further courses in the subject, and for the one who takes only one, the "terminal," course. Both pedagogically and professionally, it seems to me that the terminal course should be no less scientific than the one which is an introduction to further work. If psychology is a science, it should be presented as a science; it is at least as interesting, intellectually, as its applications, and I surely do not need to argue here that basic science is in the long run a very practical training. We would not think at the graduate level of turning out practitioners without a thorough basic training; we insist instead that a critical understanding is vital to the professional psychologist. Training in methods only, it is agreed, is a mistake. But if we give a first course which is primarily concerned with personal adjustment and the like, we are making precisely that mistake. The function of the course instead should be to develop critical understanding, to prepare the student to evaluate his later reading in the field of method, and prepare him also to understand the new methods that will be developed after he has left his "terminal" course. Valuable as the practical methods of psychology now are, I believe that those of the future will be more valuable still; if so, the theoretical and academic course isas I have said abovethe most practical one in the long run. In the references to be found in the Notes at the end of each chapter, I have chosen primarily to refer to textbooks; and especially to the three handbooks of general experimental psychology. For the more advanced student who may wish to use the book, however, I have also given some references to the original literature"--Preface. (PsycINFO Database Record (c) 2012 APA, all rights reserved)
Keywords: Psychologie; Psychology; psychology